2021
DOI: 10.1101/2021.01.13.426558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular dynamic simulation reveals E484K mutation enhances spike RBD-ACE2 affinity and the combination of E484K, K417N and N501Y mutations (501Y.V2 variant) induces conformational change greater than N501Y mutant alone, potentially resulting in an escape mutant

Abstract: Rapidly spreading SARS-CoV-2 variants present not only an increased threat to human health due to the confirmed greater transmissibility of several of these new strains but, due to conformational changes induced by the mutations, may render first-wave SARS-CoV-2 convalescent sera, vaccine-induced antibodies, or recombinant neutralizing antibodies (nAbs) ineffective. To be able to assess the risk of viral escape from neutralization by first-wave antibodies, we leveraged our capability for Molecular Dynamic (MD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
236
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(249 citation statements)
references
References 22 publications
12
236
0
1
Order By: Relevance
“…It is found that the residue Glu484 is located on a flexible loop of RBD, and the substitution of Glu484 by Lys leads to obvious conformational movements of the flexible loop towards the receptor hACE2, which results in the more tight binding between RBD and hACE2. Our simulation results are consistent with the simulation results of Nelson [33]. Therefore, the conformational rearrangements of the binding interface caused by the mutation result in the decrease of the van der Waals and the polar desolvation energies.…”
Section: Results and Discussion E484k Mutation Enhances The Binding Asupporting
confidence: 90%
See 1 more Smart Citation
“…It is found that the residue Glu484 is located on a flexible loop of RBD, and the substitution of Glu484 by Lys leads to obvious conformational movements of the flexible loop towards the receptor hACE2, which results in the more tight binding between RBD and hACE2. Our simulation results are consistent with the simulation results of Nelson [33]. Therefore, the conformational rearrangements of the binding interface caused by the mutation result in the decrease of the van der Waals and the polar desolvation energies.…”
Section: Results and Discussion E484k Mutation Enhances The Binding Asupporting
confidence: 90%
“…Fortunately, the sera neutralization assay showed that the N501Y mutation has little effect on the neutralization of the human sera elicited by the BNT162b2 mRNA vaccine [25]. In the 501Y.V2 and 501Y.V3 variants, besides the N501Y mutation, two other mutations E484K and K417N (or K417T) were occurred in RBD of the S protein, and it is revealed that the E484K mutation obviously enhances the binding affinity between RBD and hACE2 [33].…”
Section: Introductionmentioning
confidence: 99%
“…It creates a new site for the amino acid 75 hACE-2 binding. This interaction seems even stronger than the binding between hACE-2 and the original main site located at position 501 (at RBD and hACE-2 interface) (Nelson et al, 2021) . We speculate that the consequent neutralization escape due to E484K alone or as a part of a larger array of distinct mutations might act as a common evolutionary solution for several different viral lineages.…”
Section: Introductionmentioning
confidence: 86%
“…To the best of our knowledge, the impact of E484K in different lineages have not been deeply explored. It was structurally demonstrated that, at least in combination with K417N and N501Y, the substitution has profound impact in shifting the main site of contact between viral RBD and hACE-2 residues (Nelson et al, 2021) . However, we still do not know if this holds true for other sets of mutations associated with E484K.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation